Estrategias de afrontamiento y calidad de vida en pacientes geriátricos con dolor crónico del Cantón Gonzanamá - Condo Muñoz, Stalin Enrique (2024)
Coping in the face of pain is defined as the combination of cognitive and behavioral efforts used to control pain; the cognitive component refers to intellectual efforts, such as perseverance in ignoring pain; while behavioral efforts are pain-related activities, such as the decrease or increase in the medication. The objective of this study was to determine coping strategies and quality of life in geriatric patients with chronic pain of Gonzanamá Canton. It was realized of quantitative, descriptive, prospective, and cross-sectional approach. The study area was Gonzanamá Canton, where 84 older adults with chronic pain participated, the technique applied was the survey, for this purpose, it was employed a questionnaire made up of three sections (sociodemographic data, WHOQOL-BREF quality of life scale and chronic pain coping scale). The results demonstrate that the most frequently used coping strategy is religion with 89%, which belongs to the adequate coping of passive type. 77,0% state a low-quality life level, followed by medium (19,0%) and high (4,0) quality life level. Those of advanced age (65-70 years) stand out with 76%, male sex (79%), elementary education (73%), marital status: married (81%), with occupation mostly retired (92%), without health insurance (84%) and all participants belong to the Catholic religion. It is concluded that the most used strategy is religion, which involves faith and a feeling of divine protection, in addition, they perceive a low life quality complexly influenced by physical health, physiological state, degree of self-control and social relations and with their environment